Gen-Z lifestyle trigger of indigenous fabric users @padupadantenun stimulates by brand ambassador differences - Guru, Elisabet; Marta, Rustono Farady; Engliana; Nurhayati, Kristina; Mandaru, Silvania Stella Epiphania (Program Studi Ilmu Komunikasi, 2025)
This study analyzes the influence of trust values ​​towards brand ambassadors Prilly Latuconsina (X1) and Bryan Domani (X2) on Generation Z's lifestyle in using traditional fabric products, especially through interactions on the Instagram account @padupadantenun. The method used is a quantitative survey with data collection through questionnaires, which are analyzed using the t-test and SPSS. The results of the study indicate that trust values ​​towards brand ambassadors have a significant effect on Generation Z's lifestyle in adopting traditional fabrics. The higher the consumer's trust in the brand ambassador, the greater the positive influence on their decisions. These findings provide strategic insights for the marketing industry in developing effective social media-based promotional strategies to reach Generation Z and encourage cultural preservation with a modern approach.